Nt-probnp level changes after combination therapy with bisoprolol and ace-inhibitor in patient with heart failure - Risthanti, Reine Risa; Aminuddin, Muhammad; Suharjono, Suharjono (Folia Medica Indonesiana, 2017)
Heart failure (HF) is the final common stage of many diseases of the heart. NT-proBNP levels are increased in HF and correlate well with ventricular wall stress and severity of HF. Combination therapy with Bisoprolol and ACE-inhibitor decreases NT-proBNP level in patient with HF. The use of Bisoprolol as a combination with ACE-inhibitor is still dominate in outpatient setting at Dr. Soetomo teaching hospital. The objective of this study is to analyze NT-proBNP level changes as an indicator in cardiac function after combination therapy with Bisoprolol and ACE-inhibitor in patient with HF.Methods: This study was prospective, observational and conducted in outpatient setting. Consecutive patients who meet the inclusion criteria of the study were included. Blood samples were taken at pre and 2 months post combination therapy with Bisoprolol and ACE-inhibitor, then NT-proBNP level was measured with IMMULITE®. There were 14 patients enrolled in this study (7 males, 7 females). The result showed that NT-proBNP 2 months post combination therapy with Bisoprolol and ACE-inhibitor is significantly decreased than baseline with mean baseline of NT-proBNP level is 4191.43 ± 4367.277 pg/ml to 2786.79 ± 2485.199 pg/ml (p=0.025). From a total 14 patients, 9 patients had NT-proBNP decreases >20% (20.1% – 56.4%) and 3 patients had NT-proBNP decreases <20% (1.8%, 6.6%, and 12.4%). There were 2 patients with NT-proBNP increases >40% (43.4% and 40.4%). In conclusion, there was a significant decreases in NT-proBNP level after 2 months combination therapy with Bisoprolol and ACE-inhibitor in patient with HF.